Perbandingan Antara Neuro Developmental Treatment (NDT) Dengan Kombinasi NDT Dan Sensory Integration Untuk Meningkatkan Keseimbangan Berdiri Pada Anak Berkebutuhan Khusus - Prasaja Prasaja; Khomarun Khomarun (Jurnal Keterapian Fisik, 2017)
Abstract: Comparison of NDT, Combined NDT & SI, Standing-Balance. There upon, the purposes of the study are: (1) to determine the effects of NDT in the standing- balance trainings, (2) to determine the effects of combined NDT and Sensory Integration application in standing-balance training, (3) to compare the effects of treatment a combined NDT and sensory integration application versus sole NDT application in standing-balance training for children with special needs. The study is a pre and post-test experimental study design that compares two treatment groups. The first group received solely the NDT applications only while the other one received a combined NDT and sensory integration approach as the treatments. Sixteen Balance Test was used as a measurement instruments, which were conducted prior to and following the treatments in each group. Data were analyzed with the use of the parametric pair wise comparison test (paired sample t-test) and a parametric test(independent sample t-test) was used to investigate the compatibility of the data in the two groups before treatments. The last and above test was conducted adjacent to the fact that normal data distribution was founded. The study results are: (1) a sole NDT application improves the standing-balance ability amongst the children (p = 0.000). (2)The combination of NDT methods and Sensory Integration improves the standing- balance ability amongst children with special needs (p = 0.000). (3) The combination of NDT methods and Sensory Integration is proven to be better in developing standing- balance ability than just sole applications of NDT methods; in terms of improvingstanding-balance ability (p = .0.002) within children with special needs